(untitled) - Solomon, Norman (Hoboken, N.J., 2005)
War Made Easy exposes and explains the lies and deceptions that have misled our nation into vile and bloody disasters from Vietnam to El Salvador to Iraq; it reveals the frequent cowardice and culpability of the US media that often behaves as a propaganda arm of the Pentagon.
Keywords: War,Press and politics,Government and the press,Chiến tranh,Báo chí và chính trị,Chính quyền và báo chí; Press coverage,Tin tức báo chí; United States,United States,United States,Hoa Kỳ,Hoa kỳ